The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1037/0003-066x.44.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Marital transitions: A child's perspective.

Abstract: Despite a recent leveling off of the divorce rate, almost half of the children born in the last decade will experience the divorce of their parents, and most of these children will also experience the remarriage of their parents. Most children initially experience their parents' marital rearrangements as stressful; however, children's responses to their parents marital transitions are diverse. Whereas some exhibit remarkable resiliency and in the long term may actually be enhanced by coping with these transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
1
10

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(221 citation statements)
references
References 35 publications
(74 reference statements)
7
200
1
10
Order By: Relevance
“…Temperamento e nível de desenvolvimento são dimensões intrínse-cas à criança, essenciais na compreensão do processo de adaptação à separação ou divórcio parental [21][22][23][24][25] . Crianças com temperamento fácil, inteligentes, responsáveis e socialmente sensíveis evidenciam mais competência de adaptação positiva a essa transição familiar 24 .…”
Section: Características Da Criançaunclassified
“…Temperamento e nível de desenvolvimento são dimensões intrínse-cas à criança, essenciais na compreensão do processo de adaptação à separação ou divórcio parental [21][22][23][24][25] . Crianças com temperamento fácil, inteligentes, responsáveis e socialmente sensíveis evidenciam mais competência de adaptação positiva a essa transição familiar 24 .…”
Section: Características Da Criançaunclassified
“…Hetherington (1979Hetherington ( , 1984 suggested that children of different ages differ in their awareness of and ability to cope with interparental conflict, but that no one particular age group is likely to be more affected than another. Although young children may be less able to cope with conflict, they are less likely to be aware of conflict and its implications, whereas older children have a larger repertoire of coping responses but are likely to be more aware of the causes and consequences of conflict (Hethering-ton, 1984;Hetherington, Stanley-Hagen, & Anderson, 1989). This idea has been supported by work on children's response to anger between adults, which shows that 4-to 5-year-old children evidence more distress, but also more adaptive coping responses, than 2-to 3-year-olds (E. M. Cummings, 1987).…”
Section: Demographic Variablesmentioning
confidence: 99%
“…Hetherington et al 5,[10][11][12] enfatizaram consistentemente duas dimensões intrínsecas às crianças, essenciais no processo de adaptação à separação: o temperamento e o nível de desenvolvimento. As crianças com temperamento fácil, inteligentes, responsáveis e socialmente sensíveis são as que evidenciam melhor capacidade de adaptação positiva a esta transição familiar 5 .…”
Section: Características Individuais Da Criançaunclassified